Remediation of Groundwater Contaminated with Copper Ions by Waste Foundry Sand Permeable Barrier (Journal of Engineering, 2014)
The permeable reactive barrier (PRB) is one of the promising innovative in situ groundwater remediation technologies, in removing of copper from a contaminated shallow aquifer. The 1:1- mixture of waste foundry sand (WFS) and Kerbala’s sand (KS) was used for PRB. The WFS was represented the reactivity material while KS used to increase the permeability of PRB only. However, Fourier-transform infrared (FTIR) analysis proved that the carboxylic and alkyl halides groups are responsible for the sorption of copper onto WFS. Batch tests have been performed to characterize the equilibrium sorption properties of the (WFS+KS) mix in copper- containing aqueous solutions. The sorption data for Cu+2 ions, obtained by batch experiments, have been subjected to the Langmuir and Freundlich isotherm models. The Langmuir model was chosen to describe the sorption of solute on the solid phase of PRB. COMSOL Multiphysics 3.5a based on finite element method was used for formulation the transport of copper ions in two- dimension physical model under equilibrium condition. Numerical and experimental results proved that the PRB plays a potential role in the restriction of the contaminant plume migration. A good agreement between the predicted and experimental results was recognized with mean error (ME) not exceeded 10 %.